The Third and First-Person Effects of Election Polling News Through Emotions - Hyunjung Kim (Asian Journal for Public Opinion Research)
In this study, we examine how the third- and first-person perceptions of election polling news are linked to voters’ political behaviors through anxiety and pride. The results of two web-based surveys conducted before and after the 2022 local elections in South Korea demonstrate that the third-person perception of election polling news is directly and indirectly linked to support for restrictions on media reports of election poll results through anxiety. The first-person perception of polling news is positively associated with reinforcement of support for the preferred candidate. These results suggest that how voters perceive the effects of polling news may have actual impacts on their political behaviors.